GSH-depleting and H2O2-self-supplying hybrid nanozymes for intensive catalytic antibacterial therapy by photothermal-augmented co-catalysis. (1st January 2023) - Li, Junqin; Yi, Wenhua; Luo, Yuze; Yang, Ke; He, Lidan; Xu, Caiyun; Deng, Le; He, Dinggeng
Abstract: Nanozyme-based chemodynamic therapy (CDT) has shown tremendous potential in the treatment of bacterial infections. However, the CDT antibacterial efficacy is severely limited by the catalytic activity of nanozymes or the infection microenvironments such as insufficient hydrogen peroxide (H2 O2 ) and overexpressed glutathione (GSH). Herein, a versatile hybrid nanozyme (MoS2 /CuO2 ) is rationally constructed by simply decorating ultrasmall CuO2 nanodots onto lamellar MoS2 platelets of hydrangea-like MoS2 nanocarrier via a covalent Cu-S bond. The MoS2 /CuO2 nanozyme exhibits the peroxidase-mimic activity for catalytically converting H2 O2 produced by acid-triggered decomposition of the decorated CuO2 into hydroxyl radical (OH). Meanwhile, the MoS2 /CuO2 can consume GSH overexpressed in the infection sites via redox reaction mediated by polyvalent transition metal ions (Cu 2+ and Mo 6+ ) for enhanced CDT. More importantly, MoS2 support can promote the conversion of Cu 2+ to Cu + by a co-catalytic reaction based on the Mo 4+ /Mo 6+ redox couples, and provide photonic hyperthermia (PTT) to augment the peroxidase-mimic activity. The developed MoS2 /CuO2 nanozymes possesses a desirable catalytic property, as well as a remarkably improved antibacterial efficiency both in vitro and in vivo . Taken together, this study proposes a synergetic multiple enhancement strategy to successfully construct the versatile hybrid nanozymes for intensive in vivo PTT/CDT dual-mode anti-infective therapy. Statement of significance: Chemodynamic therapy (CDT) has shown great potentialities in the treatment of bacterial infections, while its therapeutic efficiency is severely limited by the infection microenvironments such as insufficient hydrogen peroxide (H2 O2 ) and overexpressed glutathione (GSH). Here, we rationally construct a hybrid nanozyme (MoS2 /CuO2 ) with peroxidase-like activity that can enhance CDT by regulating local microenvironments, that is, simultaneously self-supplying H2 O2 and consuming GSH. Importantly, MoS2 support can promote the conversion of Cu 2+ to Cu + by the Mo 4+ /Mo 6+ redox couples, and provide photonic hyperthermia (PTT) to augment the peroxidase-mimic activity. The developed MoS2 /CuO2 shows desirable PTT/CDT dual-mode antibacterial efficacy both in vitro and in vivo . This study proposes a versatile hybrid nanozyme with multiple enhancement effects for intensive in vivo anti-infective therapy. Graphical abstract: Image, graphical abstract